2023
DOI: 10.1021/acs.inorgchem.3c03635
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Optimization of Crystal Facets and Nanoscale Spatial Confinement toward the Boosted Catalytic Performance of Pd Nanocrystals

Dongling Wang,
Chengchao Zhang,
Lichun Zhang
et al.

Abstract: Tuning the surface chemical property and the local environment of nanocrystals is crucial for realizing a high catalytic performance in various reactions. Herein, we aim to elucidate the structure sensitivity of Pd facets on the surface catalytic hydrogenation reaction and to identify what role the nanoconfinement effect plays in the catalytic properties of Pd nanocrystal catalysts. By controlling the coating structures of mesoporous silica (mSiO 2 ) on Pd nanocrystals with different exposed facets that includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 80 publications
0
2
0
Order By: Relevance
“…Recent investigations on hetero-catalytic reactions indicated that the presence of metal catalysts in a yolk–shell coating structure could significantly enhance their catalytic performance. 30–36 However, not much is known about the thermal stability of yolk–shell structures although the different geometry likely alters the thermal stability and reshaping mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…Recent investigations on hetero-catalytic reactions indicated that the presence of metal catalysts in a yolk–shell coating structure could significantly enhance their catalytic performance. 30–36 However, not much is known about the thermal stability of yolk–shell structures although the different geometry likely alters the thermal stability and reshaping mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, the synthesis of high-index-faceted nanocrystals (NCs) has paid intense attention to their excellent electrocatalytic performances to generate sustainable fuels. For example, tetrahexahedral Pt nanocrystals exposed with 24 high-index {730} facets showed a 330% enhanced current density toward ethanol electrooxidation . The specific activity of concave Pd trisoctahedra exposed with {441} facets was 3.1-fold higher than that of Pd octahedra toward formic acid electrooxidation .…”
Section: Introductionmentioning
confidence: 99%